In-process thermal treatment of polylactic acid in fused deposition modelling. Issue 6 (26th April 2019) - Harris, Muhammad; Potgieter, Johan; Archer, Richard; Arif, Khalid Mahmood
ABSTRACT: Polylactic acid (PLA) is one of the most widely used open source fused filament fabrication materials due to its ease of extrusion, biodegradability, and mechanical strength. The mechanical strength of PLA largely depends on the proper growth of its semi-crystalline structure, which can be severely impaired by a low rate of crystallization, particularly in open source printers. This can be further aggravated by the non-uniform thermal distribution of heat that causes improper curing among the extruded beads of the printing material. As a result, PLA printed on open source printers does not achieve the best mechanical properties. This research, for the first time, proposes an additive-free solution implemented through a detailed set of experimentation to improve the curing rate through in-process temperature variations to cure the joints among the beads. Scanning electron microscopy (SEM), differential scanning calorimetry (DSC) and Fourier transform infrared (FTIR) spectroscopy is used to confirm the improvements in the bead joints. This work is conducted in two phases of experiments. In the first phase, a full factorial ANOVA is used to investigate various process parameters and the important variables are used in the second phase to print test specimens in four different sets.